2020
DOI: 10.1029/2020jb020443
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Cr‐Rich Spinel in Serpentinized Ultramafic Complexes

Abstract: In comparison to the six spinel end-members in the spinel prism, magnetic information on the intermediate spinel compositions is relatively poorly established. To investigate magnetic properties of intermediate compositions of Cr-rich spinel, we collected 12 samples that might contain potentially magnetic Cr-rich spinel. On the basis of chemical composition analysis and physical magnetic behavior, magnetic Group A Fe-rich spinel (i.e., magnetite), magnetic Group B Cr-rich spinel, and paramagnetic Group C Cr-Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 134 publications
0
3
0
Order By: Relevance
“…Previous studies reported that chrome‐rich spinel is ferrimagnetic (Kądziałko‐Hofmokl et al., 2008; Rais et al., 2003), however, this phase generally owes its magnetization to magnetite inclusions or exsolution features, while common chrome‐rich spinels are paramagnetic above 70 K at 1 atm (Gattacceca et al., 2011). Furthermore, chrome‐rich spinel is ferrimagnetic only if (Al 2 O 3 + MgO)/(Cr 2 O 3 + FeO + Fe 2 O 3 ) < 0.1 (Yu & Tikoff, 2020), a condition that is not met in the Cima di Gratera chrome spinels (Andersen & Austrheim, 2006). Hence chrome‐rich spinel is paramagnetic in these pseudotachylytes.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that chrome‐rich spinel is ferrimagnetic (Kądziałko‐Hofmokl et al., 2008; Rais et al., 2003), however, this phase generally owes its magnetization to magnetite inclusions or exsolution features, while common chrome‐rich spinels are paramagnetic above 70 K at 1 atm (Gattacceca et al., 2011). Furthermore, chrome‐rich spinel is ferrimagnetic only if (Al 2 O 3 + MgO)/(Cr 2 O 3 + FeO + Fe 2 O 3 ) < 0.1 (Yu & Tikoff, 2020), a condition that is not met in the Cima di Gratera chrome spinels (Andersen & Austrheim, 2006). Hence chrome‐rich spinel is paramagnetic in these pseudotachylytes.…”
Section: Discussionmentioning
confidence: 99%
“…Natural samples of oceanic peridotites are typically heavily altered and the primary textures and mineralogic associations are not preserved, except for spinel (Yu and Tikoff, 2020). Alteration results from the chemical and mineralogic changes that occur during the interaction between ultramafic rocks and seawater and/or hydrothermal fluids.…”
Section: Introductionmentioning
confidence: 99%
“…Hounslow (1996) reported that ferrimagnetic Fe-Cr and Fe-Mn spinels are the dominant remanence carrying phases in the Lunde Formation, North Sea. And the Fe-Cr spinel is also a potential carrier of a natural remanent magnetization (NRM) and a source of magnetic anomalies in ultramafic complexes (Yu & Tikoff, 2020). From sediments which are dominated by ferrous ilmenites, (titano-)magnetite, Cr-Fe spinels, and impure magnetite, Scheidt et al (2017) also reconstructed a reliable magnetic polarity stratigraphy.…”
mentioning
confidence: 99%